Cardiovascular Pharmacological Studies on JTV-506, a New Potassium Channel Opener 2nd Communication: Effects on blood pressure in conscious animals - Hirata, Yukiya; Suzuki, Yasunori; Miyai, Hisato; Aisaka, Kazuo (Arzneimittelforschung, 2000)
The effects of JTV-506 ((−)-(3S,4R)-2,2-bis(methoxymethyl)-4-[(l,6-dihydro-1-methyl-6-oxo-3-pyridazinyl)amino]-3-hydroxychroman-6-carbonitrile hemihydrate, CAS 170148-29-5), a novel coronary vasodilator, on blood pressure were evaluated in conscious dogs and rats. In conscious dogs, JTV-506 (0.01–1 mg/kg p.o.), levcromakalim (0.01–1 mg/kg p.o.) and nifedipine (3–30 mg/kg p.o.) elicited an increase in double product, whereas nicorandil (1–10 mg/kg p.o.) did not affect the double product. The JTV-506-induced increase in double product was abolished by a ß-blocker, propranolol, suggesting that this increase in double product may be due to augumentation of heart rate by sympathetic nerves which mediate the baroreflex. The doses at which JTV-506 increased coronary blood flow in a previous study were lower than the doses required to increase the double product. JTV-506 did not have a crucial influence on electrocardiogram. In conscious rats, orally administered JTV-506, levcromakalim, nicorandil and nifedipine reduced blood pressure and increased heart rate dose dependently These effects were more remarkable in hypertensive rats than in normotensive rats. JTV-506, a new potassium channel opener, seems to be relatively free of any hemodynamic effects.
Keywords: (−)-(3S,4R)-2,2-Bis(methoxymethyl)-4-[(1,6-dihydro-1-methyl-6-oxo-3-pyridazinyl)-amino]; -3-hydroxychroman-6-carbonitrile hemihydrate; CAS 170148-29-5; JTV-506, dog, effects on blood pressure, rat; Potassium channel opener